The Discovery of Anomalous Microwave Emission - Erik M. Leitch; A. C. R. Readhead (Advances in Astronomy)
We discuss the first detection of anomalous microwave emission, in the Owens Valley RING5M experiment, and its interpretation in the context of the ground-based cosmic microwave background (CMB) experiments of the early 1990s. The RING5M experiment was one of the first attempts to constrain the anisotropy power on sub-horizon scales, by observing a set of -size fields around the North Celestial Pole (NCP). Fields were selected close to the NCP to allow continuous integration from the Owens Valley site. The experiment detected significant emission at both 14.5 GHz and 30 GHz, consistent with a mixture of CMB and a flat-spectrum foreground component, which we termed anomalous, as it could be explained neither by thermal dust emission, nor by standard models for synchrotron or free-free emission. A significant spatial correlation was found between the extracted foreground component and structure in the IRAS 100 μm maps. While microwave emission from spinning dust may be the most natural explanation for this correlation, spinning dust is unlikely to account for all of the anomalous emission seen in the RING5M data.